Home Blood Pressure Monitoring Devices: Device Performance in an Alaska Native and American Indian Population. (August 2021) - Schaefer, Krista R.; Fyfe-Johnson, Amber L.; Noonan, Carolyn J.; Todd, Michael R.; Umans, Jason G.; Castille, Dorothy M.; Rosenman, Robert; Buchwald, Dedra S.; Dillard, Denise A.; Robinson, Renee F.; Muller, Clemma J.
Objectives: Home blood pressure monitoring (HBPM) is an important component of blood pressure (BP) management. We assessed performance of two HBPM devices among Alaska Native and American Indian people (ANAIs).Methods: We measured BP using Omron BP786 arm cuff, Omron BP654 wrist cuff, and Baum aneroid sphygmomanometer in 100 ANAIs. Performance was assessed with intraclass correlation, paired t -tests, and calibration models.Results: Compared to sphygmomanometer, average BP was higher for wrist cuff (systolic = 4.8 mmHg and diastolic = 3.6 mmHg) and varied for arm cuff (systolic = −1.5 mmHg and diastolic = 2.5 mmHg). Calibration increased performance from grade B to A for arm cuff and from D to B for wrist cuff. Calibration increased false negatives and decreased false positives.Discussion: The arm HBPM device is more accurate than the wrist cuff among ANAIs with hypertension. Most patients are willing to use the arm cuff when accuracy is discussed.